Importance of freeze-thaw events in low temperature ecotoxicology of cold tolerant enchytraeids - Patrício Silva, Ana L.
Due to global warming it is predicted that freeze-thaw cycles will increase in Arctic and cold temperate regions. The effects of this variation becomes of particular ecological importance to freeze-tolerant species when it is combined with chemical pollutants. We compared the effect of control temperature (2 °C), daily freeze-thaw cycles (2 to -4 °C) and constant freezing (-2 °C) temperatures on the cold-tolerance of oligochaete worms (Enchytraeus albidus) and tested how survival was influenced by pre-exposure to 4-nonylphenol (4-NP), a common nonionic detergent found in sewage sludge amended soils. Results showed that combined effect of 4-NP and daily freeze-thaw cycles can cause higher mortality to worms as compared with sustained freezing or control temperature. Exposure to 4-NP caused a substantial depletion of glycogen reserves which is catabolized during freezing to produce cryoprotective concentrations of free glucose. Further, exposure to freeze-thaw cycles resulted in higher concentrations of 4-NP in worm tissues as compared to constant freezing or control temperature (2 °C). Thus, worms exposed to combined effect of freeze-thaw cycles and 4-NP suffer higher consequences, with the toxic effect of the chemical potentiating the deleterious effects of freezing and thawing.